Traising Pesantren Poetry as a Cirebon Teaching Material, Study of Nadoman Poetry Text Structure in The Aurodan Tradition of AsySyahadatain Cirebon - SA. Maskur; Sumiyadi Sumiyadi; Iskandarwassid, Iskandarwassid; Permadi Tedi (International Conference on Elementary Education, 2020)
Oral tradition is a legacy passed down from ancestors to later generations through speech media. Nadoman in the Aurodan tradition of the Asy-Syahadatain Congregation in Cirebon is part of an oral tradition in the form of an oral poem in the Cirebon language that is used for the media of the preaching of the chaplain which is usually sung in the form of singing during the rituals of dhikr together. Aurod is a book in which nadoman poetry is read together in an Aurodan tradition developed as the tradition of the Munjul Islamic Boarding School in Cirebon. Auordan and Nadoman are very thick with the Cirebon Islamic culture which is flexible, gentle, open, tolerant, as a product of acculturation of several cultures, namely Javanese Islam, Sundanese, Arabic, and even other cultures in Cirebon, even though it was born from ulama leaders who are identical and closed. This study aims to examine the structure of the nadhoman poetry text in the oral tradition of the Aurodan Praise of the Prayer of the Noble Congregation of the Asy-Syahadatain Congregation of Cirebon. This research is a qualitative research. Qualitative methods are used to examine objects in natural conditions, to find meaning and generalization, where the researcher as a key instrument. This study was designed to describe, analyze, reveal, and explain the structure of Nadoman poetry texts in the Aurodan tradition of the Asy-Syahadatain Cirebon Cirebon. This study uses basic data which includes (1) the structure of the nadhoman poetry text in the oral traditions of the Aurodan Congregation of the As-Syahadatain Cirebon Cirebon which were sung as praises of prayer before prayer; (2) efforts to use it in learning Cirebon Literature at school. Tenik Data collection is done by observation, interviews, document studies. The results of this study found some very beautiful niroman cirebon poems and conditions for value and worth to be raised in as one of Cirebon’s cultural heritage, and Nusantara’s cultural heritage in general by incorporating it into the school curriculum as teaching material